Assessing the potential of marine Natura 2000 sites to produce ecosystem‐wide effects in rocky reefs: A case study from Sardinia Island (Italy). Issue 4 (19th February 2019) - Guidetti, Paolo; Addis, Piero; Atzori, Fabrizio; Bussotti, Simona; Calò, Antonio; Cau, Alessandro; Culioli, Jean‐Michel; De Lucia, Giuseppe; Di Franco, Antonio; Di Lorenzo, Manfredi; Follesa, Maria Cristina; Gazale, Vittorio; et al.
Abstract: A number of policy measures have been adopted to cope with ongoing ocean degradation. Marine protected areas (MPAs) are among them. MPAs and their coverage have increased worldwide, including in EU waters. Natura 2000 (Nat2000) sites are at the core of the EU biodiversity conservation strategy and have been established to protect habitats and species included in two EU directives. Besides their specific objectives, their potential to contribute to an ecosystem‐wide conservation and their complementarity with other national and supranational initiatives (e.g. nationally established MPA networks, the Marine Strategy Framework Directive, the Convention on Biological Diversity Ecosystem‐Based Approach) have been called into question. Using visual censuses on rocky reefs, the biomass of whole fish assemblages and of a set of ecologically important species (widely used as indicators of coastal marine ecosystem health) have been assessed to evaluate the potential ecosystem‐wide effectiveness of Nat2000 marine sites located along the coasts of Sardinia (Italy). The assessment was performed in six fully protected MPAs, in 12 Nat2000 sites established or extending at sea, and in 18 adjacent unprotected control sites. Results show that the highest fish biomasses are observed in fully protected MPAs. The values observed at Nat2000 sites do not differ or only slightly differ from those observed at control sites. This shows that Nat2000 sites may not presently contribute to effectively protect fish and the related rocky reef ecosystems. These results do not dismiss at all the role of Nat2000 sites relative to the objectives for which they have been established. However, they show that to achieve ecosystem‐wide benefits it is crucial to rethink and broaden the scope of Nat2000 sites and adapt their management to that. By providing sounder and more comprehensive management plans, and implementing more consistent ecosystem‐wide conservation measures, Nat2000 marine sites could become an extraordinary tool at the EU scale, capable of delivering wider ecological benefits.